Pertanggung Jawaban Pengurus Koperasi Baik Di Luar Maupun Di Dalam Koperasi Berdasarkan Undang-Undang No 25 Tahun 1992: Studi Kasus Di Koperasi Unit Desa Hemat Desa Sinunukan 4 Kec.Sinunukan Kabupaten Mandailing Natal - Ali Muddin Sirait; Dani Sintara (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
A cooperative is a joint business entity operating in the economic sector, whose members are generally those from a weak economy who join voluntarily and on the basis of equal rights, are obliged to carry out a business aimed at meeting the needs of its members. The problem in this thesis is to find out the development of cooperative regulations in Indonesia based on Law Number 25 of 1992 concerning Cooperatives, the Roles and Responsibilities of Cooperative Management and Members in the Distribution of Remaining Business Results in Thrifty Village Unit Cooperatives. The formulation of the problem that will be discussed in this thesis is: 1) What are the responsibilities of cooperative management both outside and inside the cooperative based on Law No. 25 of 1992? 2) What is the position of members in the cooperative accountability system? 3) What is the legal review of the implementation of loan agreements at the Thrifty Village Unit Cooperative? The type of research in preparing legal writing is normative legal research or library legal research. The purpose of normative legal research is research carried out by examining library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. These materials are then arranged systematically, studied and then conclusions are drawn regarding their relationship to the problems studied. Based on Article 34 of Law Number 25 of 1992 concerning Cooperatives, the responsibility of cooperative administrators as cooperative managers for cooperative losses is responsible both jointly and individually bear the losses suffered by the cooperative if the losses suffered by the cooperative are caused by intention or negligence by the cooperative management. This is closely related to the obligations imposed on cooperative management which must be based on good faith. In this case, the management of the economical village unit cooperative did not provide accountability as regulated in the Law. The role of supervisors in supervising the work of cooperative management is considered less than optimal, because they still lack knowledge and ability regarding the duties and authority for which they are responsible.